A REVIEW ARTICLE ON ROLE OF ARSHOGNA MAHAKASHAYA IN THE TREATMENT OF SUSKH ARSHA - Sharma, Sheetal; Borkar, Preeti Sujit (International Journal of Research -GRANTHAALAYAH, 2020)
Ayurvedic classical text provide unique modalities and medications among several treatises complied during ancient time. Drug is the important therapeutics as it is responsible for equilibrium of whole body. Charak Samhitha is divided into 8 parts and the first division is called Sutrasthan or shloksthan. In sutrasthan the drugs are discussed in four chapters which are popularly known as Bheshajachatushka or Aushadhachatushkha. Here the drugs are classified from pharmacological and pharmacotherapeutics perspectives. The classification of drugs based on Karmas are called Mahakashaya which are classified into fifty groups. Arshoghan Mahakashaya is the twelveth group of medicine which are said to be effective in curing piles. Sushka arsha is condition where pain and swelling of the pile mass makes life miserable for a person and bheshaj chikitsa being first in all the treatments. Here a simple effort is made to know the probable working of rasa, guna virya and prabhav of these ten drugs in dissolving the pathology of suskha arsha.